The evolution and competitive strategies of Akkermansia muciniphila in gut - Ji-Sun Kim; Se Won Kang; Ju Huck Lee; Seung-Hwan Park; Jung-Sook Lee (Gut Microbes)
Akkermansia muciniphila is a commensal bacterium using mucin as its sole carbon and nitrogen source. A. muciniphila is a promising candidate for next-generation probiotics to prevent inflammatory and metabolic disorders, including diabetes and obesity, and to increase the response to cancer immunotherapy. In this study, a comparative pan-genome analysis was conducted to investigate the genomic diversity and evolutionary relationships between complete genomes of 27 A. muciniphila strains, including KGMB strains isolated from healthy Koreans. The analysis showed that A. muciniphila strains formed two clades of group A and B in a phylogenetic tree constructed using 1,219 orthologous single-copy core genes. Interestingly, group A comprised of strains from human feces in Korea, whereas most of group B comprised strains from human feces in Europe and China, and from mouse feces. As group A and B branched, mucin hydrolysis played an important role in the stability of the core genome and drove evolution in the direction of defense against invading pathogens, survival in, and colonization in the mucus layer. In addition, WapA and anSME, which function in competition and post-translational modification of sulfatase, respectively, have been a particularly important selective pressure in the evolution of group A. KGMB strains in group A with anSME gene showed sulfatase activity, but KCTC 15667T in group B without anSME did not. Our findings revealed that KGMB strains evolved to gain an edge in the competition with other gut bacteria by increasing the utilization of sulfated mucin, which will allow it to become highly colonized in the gut environment.